Development of a Web-Based, Work-Related Asthma Educational Tool for Patients with Asthma - Shadi Ghajar-Khosravi; Susan M Tarlo; Gary M Liss; Mark Chignell; Marcos Ribeiro; Anthony J Levinson; Samir Gupta (Canadian Respiratory Journal)
BACKGROUND: Asthma is a common chronic condition. Work-related asthma (WRA) has a large socioeconomic impact and is increasing in prevalence but remains under-recognized. Although international guidelines recommend patient education, no widely available educational tool exists.